PELAKSANAAN KOMUNIKASI TERAPEUTIK OLEH PERAWAT TERHADAP PASIEN RAWAT INAP DI BADAN LAYANAN UMUM DAERAH (BLUD) RS SEKARWANGI KABUPATEN SUKABUMI - Rhodiyat Fajar Salim; Tuah Nur (Dialektika, 2017)
Therapeutic communication is a communication made by nurses as professionals that aims to help the healing process of patients. Reality is happening in BLUDs RS Sekarwangi Sukabumi, health care service users, including patients who are hospitalized there who complain of discomfort due to communication. This problem is amplified when confirmed to the public relations department of the hospital BLUDs Sekarwangi, which states that: "There are still complaints inpatients either in class II, I, even VIPs on nursing care services are less than satisfactory. The method used in the preparation of this study qualitative research. This study uses fenomenogi approach, the approach that is based on the view and the assumption that the human experience gained through interpretation. Results of the study revealed that the patient's understanding of therapeutic communication is a way of talking to the patient's nurse, the nurse as an informant about the patient's illness, how nurses with patients and nurses to chat with. Therapeutic communication techniques in the implementation by nurses, according to most patients nurse shows acceptance, offer information, and ask the patient concerned. In the stages of therapeutic communication, according to the patient from the introductory stage until the termination stage (separation) nurses do well, although not all nurses.